2021
DOI: 10.1007/s10903-021-01225-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Infectious Complications of Immunomodulation in COVID-19 in Foreign-Born Patients

Abstract: Immunomodulating therapies for COVID-19 may carry risks of reactivating latent infections in foreign-born people. We conducted a rapid review of infection-related complications of immunomodulatory therapies for COVID-19. We convened a committee of specialists to formulate a screening and management strategy for latent infections in our setting. Dexamethasone, used in severe COVID-19, is associated with reactivation of latent tuberculosis, hepatitis B, and dissemination/hyperinfection of Strongyloides species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Different algorithms [10][11][12][13][14] have been proposed to guide the risk assessment and management of SHS among patients with relevant epidemiological exposure, suffering from SARS-CoV-2 infection and requiring corticosteroids. Earlier algorithms assessed the risk and management of SHS in the case of immunosuppression in general [7,11] and can actually be adapted for the prescription of dexamethasone or other biological therapy in SARS-CoV-2-related complications.…”
Section: Screening Algorithm For Strongyloidiasismentioning
confidence: 99%
“…Different algorithms [10][11][12][13][14] have been proposed to guide the risk assessment and management of SHS among patients with relevant epidemiological exposure, suffering from SARS-CoV-2 infection and requiring corticosteroids. Earlier algorithms assessed the risk and management of SHS in the case of immunosuppression in general [7,11] and can actually be adapted for the prescription of dexamethasone or other biological therapy in SARS-CoV-2-related complications.…”
Section: Screening Algorithm For Strongyloidiasismentioning
confidence: 99%
“…Importantly, the algorithm by De Wilton et al also highlights the symptoms and signs of Strongyloides hyperinfection, such as rash, diarrhea, and respiratory deterioration with immunosuppression, which may help identify those who may have been considered to be low risk at the time of admission. Mohareb and colleagues proposed a more comprehensive screening algorithm to prevent the infectious complications of immunomodulation in foreign-born patients with COVID-19, including latent TB, hepatitis B, Chagas disease, endemic mycoses, herpesviruses, and opportunistic fungal pathogens, as well as the presumptive treatment with ivermectin for Strongyloides, unless a rapid turnaround time serologic assay is available [ 90 ]. However, the approaches mentioned above are rather specific to the context in which they were created, and are not achievable in settings that are highly endemic for Strongyloides.…”
Section: Screeningmentioning
confidence: 99%
“…It should be noted that in both HIC and LMIC settings, the decision regarding the initiation of corticosteroids for patients with severe COVID-19, thus requiring respiratory support, is a key management priority. The slow turnaround times for Strongyloides diagnostic testing, such as serologic assays at a reference laboratory, represent a significant barrier to the implementation of the proposed screening algorithms [ 85 , 90 ]. Furthermore, hospitalized patients with COVID-19 are often critically ill, which may preclude the ability to gather a full epidemiologic risk profile.…”
Section: Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Apart from corticosteroids other immunomodulators such as tocilizumab which are also commonly used in severe COVID-19 patients are also suspected to cause reactivation of a number of infections including tuberculosis. 3 Not only administration of immunomodulators but chronic conditions like diabetes is a risk factor for tuberculosis reactivation which shouldn't be overlooked. 4 Animal studies suggested that COVID-19 is itself a risk factor and responsible for the reactivation of dormant tuberculosis that further needs to be clinically correlated specially in the era when every third person is said to have tuberculosis infection in the world as per WHO.…”
Section: Introductionmentioning
confidence: 99%